A Longitudinal Study of Shop Stewards' Union Commitment and Perceptions of Union Instrumentality and Support. Issue 1 (25th November 2015) - Zacharewicz, Thomas; Martínez‐Íñigo, David; Kelloway, E. Kevin
Abstract : Although previous studies have hypothesised that union perceptions (e.g. perceived union instrumentality, perceived union support) predict members' commitment to the union, these relationships have only been tested cross‐sectionally. Drawing on attitude–behavior consistency theory, this study hypothesised that union commitment may be an antecedent of union perceptions. Cross‐lagged structural equation models with one year separating waves of data collection ( N  = 676) provided the most support for a model suggesting that commitment precedes perceptions of the union. These results point to the need to consider new models of union commitment for shop stewards and, potentially, union members.